Growth performance and carcass traits of forage-fed hair sheep wethers - Burke, J.M.; Apple, J.K. (Elsevier, 2007)
The objective of the presebt study was to compare live animal performance and carcass characteristics of ¾ or 7/8 Dorper (DO; n-30), purebred Katahdin (KA; n=20), purebred st. Croix (SC; n=17) and purebred Suffolk (SU; n=10) lambs born in the spring and fall of 2001. After weaning, lambs were supplemented with up to 680g of a corn-soybean meal supplement while grazing bermudagrass pastures overseeded with ryegrass. Lambs were slaughtered at approximately 210d of age. From birth to weaning, DO lambs gained faster (p